The Role of Management Information System in the Transportation Industry on the MAXIM Applications - Dewi Puspaningtyas Faeni; Elena Syafa Chamilla (STIKes Ibnu Sina Ajibarang, 2024)
Information systems have become important in the transportation industry, especially in the digital era like now. Transportation Tools, such as Maxim, have Utilized information technology to improve efficiency and quality of service. This research aims to understand the role of information systems in the transportation industry, with a focus on Maxim's means of transportation, and how these information technologies help improve service quality and operational efficiency.